2016
DOI: 10.1080/09712119.2015.1124339
|View full text |Cite
|
Sign up to set email alerts
|

Clinical, haematological and therapeutic studies on babesiosis in Arabian horses in the Qassim region, central of Saudi Arabia

Abstract: This study was carried out in the Qassim region, central of Saudi Arabia to determine the clinical, haematological and therapeutic impact of babesiosis caused by Babesia caballi in Arabian horses. The clinical signs in infected horses were pyrexia (40.5-41.5°C), depression, pale or icteric mucous membranes and emaciation. Haematological examination revealed significant decrease in erythrocyte, thrombocyte counts and haemoglobin concentration in infected horses compared with controls. Treatment with imidocarb d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…The erythrocytic indices (Packed Cell Volume (PCV), Haemoglobin (Hb). and Red Blood Cells (RBC) counts) in most of the studies following natural infection were found to decrease in infected animals compared with uninfected animals in both horses and donkeys [44,46]. Erythrocytic parameters such as Mean Capsular Volume (MCV), Mean Capsular Haeemoglobin (MCH).…”
Section: Clinical Manifestationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The erythrocytic indices (Packed Cell Volume (PCV), Haemoglobin (Hb). and Red Blood Cells (RBC) counts) in most of the studies following natural infection were found to decrease in infected animals compared with uninfected animals in both horses and donkeys [44,46]. Erythrocytic parameters such as Mean Capsular Volume (MCV), Mean Capsular Haeemoglobin (MCH).…”
Section: Clinical Manifestationsmentioning
confidence: 99%
“…Erythrocytic parameters such as Mean Capsular Volume (MCV), Mean Capsular Haeemoglobin (MCH). and Mean Capsular Haemoglobin Concentration (MCHC) were variable with notable increases in the concentration of MCH and MCHC in most of the studies [44,46]. Thrombocytopenia has been observed in several studies of clinical EP [47,48].…”
Section: Clinical Manifestationsmentioning
confidence: 99%
“…To determine plasmatic levels of testosterone, blood samples of cryptorchid horses were collected by left jugular into heparinized vacutainer ® (BD, Madrid, Spain) tubes under standard protocol (Osman 2017). Two samples were taken (at 9.00-10.00 am and 4.00-6.00 pm) from each horse.…”
Section: Endocrine Evaluationmentioning
confidence: 99%